In Vitro Anthelmintic Activity of Acalypha Indica Leaves Extracts - Diah Titik Mutiarawati (Humanistic Network for Science and Technology (HNST), 2020)
Anting-anting leaves (Acalypha indica L) is one of the wild plants (weeds) that are often used by the community to treat helminthic diseases such as ascariasis, containing several potentially anthelmintic compounds, namely saponins, tannins and flavonoids. The purpose of this study was to determine the effect of giving Anting-anting leaf extract (Acalypha indica L) as an anthelmintic to the time of death of pork roundworms (Ascaris suum Goeze). The method in this study was pre-experimental with a post test only group design. The subjects of the study were Ascaris suum. The study was conducted at the Parasitology Laboratory of the Surabaya Polytechnic Health Medical Laboratory Technologist Department in December-May 2018. This study used 5 treatment groups, 0.9% NaCl as negative control and 0.25% pirantel pamoate as positive control and 60%, 80% and 100%. Data were analyzed using the Kolmogrov-Smirnov test, then the Kruskal-Wallis test was then continued using a Post-Hoc test to determine the difference in anthelmintic power of ear leaf extract of each concentration with positive control over the time of worm death. The average time of Ascaris suum worm death at a concentration of a concentration of 60% for 228.5 minutes, a concentration of 80% for 174 minutes, and a concentration of 100% for 92 minutes. So it can be concluded that the leaf extract of Acalypha L has an anthelmintic effect on the Ascaris suum worm. Keywords: anthelmintic; Ascaris suum; anting-anting leaf